Individual Characteristics and Locus of Control as Factors Related to Burnout in Nurses: Non - Antonius Ngadiran; Mona Rentalui; Roselina Tambunan; Dalia Novita Sari; Rosmawati Napitupulu; Kristoforus Triantono; Pangindenan Sinuraya (JKG (JURNAL KEPERAWATAN GLOBAL), 2025)
Background: Burnout is a condition of extreme fatigue and exhaustion that is widely experienced by workers. Nurses who work on the front line for 24 hours are at high risk of burnout, which can jeopardise their wellbeing as well as patient safety and quality of care. This study aims to identify the dominant factors, including individual characteristics, work environment, locus of control, and work experience, that influence burnout among hospital nurses. Methods: The study used a cross-sectional study was conducted to evaluate the level of burnout. The sample was 431 nurses who was selected from the hospital using stratified random sampling to ensure the representation of different work units or departments. Date analysis was performed using Structured Equation Modelling (SEM) to examine the complex relationships between the variables. Results: The results of the bivariate analysis indicate that there is a relationship between respondent characteristics and nurse burnout incidence. A significant negative relationship was found between the work environment and burnout occurrence, as well as a relationship between years of work experience and burnout incidence. Meanwhile, the results of the multivariate analysis showed that characteristics, work environment, locus of control, and work experience influence burnout by 10.9%. Conclusion: This study shows that the variables of characteristics, work environment, locus of control, and work experience account for 10.9% of the burnout. This study recommends improving the work environment, strengthening locus of control, and providing mentoring for nurses with low experience to prevent burnout.